La muñequita zapatista: significación social de un objeto icónico artesanal. Issue 3 (3rd July 2022) - Varela Mattute, Ambar
ABSTRACT: Indigenous women have fulfilled a fundamental role in the Zapatista movement. This article focuses on the ways in which the making of handicrafts makes possible for them to connect with people around the world through the ideals of their struggle, making those ideas their own. I reflect on a particular set of objects: those engraved with the image of a woman with her face behind a ski mask (el pasamontañas) and braided hair over her shoulders: the Zapatista doll (la muñequita zapatista). This image (whether it is printed, embroidered or drawn on various surfaces) condenses the struggles of indigenous women in the movement, allowing for women all over the world to identify with them (despite differences in age, race, and occupational background) as an echo of their own daily struggles in a feminist code (both politically and in daily life contexts). As a result, the Zapatista doll embraces different social meanings that constitute an ideal of 'self-worthy and rebellious woman' (la mujer digna y rebelde) that becomes a common symbol for both the artisans and the women in their struggle against machismo culture. This ideal image allows for dialogue in the different settings in which women develop their day-to-day strategies of resistance and resilience. By manufacturing or wearing the objects, women are able to unify their struggle for autonomy and share a message of mutual encouragement beyond borders.